FRI0174 SUBCUTANEOUS DOSING OF THE NOVEL ANTI-CD40 ANTIBODY ISCALIMAB ACHIEVES TARGET DRUG EXPOSURE AND CLINICAL EFFICACY IN PRIMARY SJÖGREN'S SYNDROME; RESULTS OF A PHASE IIA RANDOMISED OPEN LABEL TWO ARM PARALLEL GROUP TRIAL. (June 2019) - Fisher, Benjamin; Szántó, Antónia; Ng, Wan Fai; Bombardieri, Michele; Posch, Maximilian; Papas, Athena; Farag, Arwa; Daikeler, Thomas; Bannert, Bettina; Kivitz, Alan; Carsons, Steven; Isenberg, David; et al.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic progressive autoimmune disease characterised by formation of lymphoid structures and germinal centres within glandular tissue. Iscalimab (CFZ533) is a novel monoclonal antibody that potently and selectively blocks CD40, a co-stimulatory pathway receptor important for germinal centre reactions and B cell activation. Iscalimab showed clinical efficacy in a Proof of Concept randomised controlled trial at a dose of 10 mg/kg intravenously (IV), whereas subcutaneous (SC) dosing at 3 mg/kg was associated with unexpectedly low plasma concentrations and reduced efficacy, likely due to efficient pre-systemic target-mediated clearance. Objectives: To test IV versus SC loading doses of iscalimab followed by SC maintenance dosing, as a means of achieving target drug exposure and clinical efficacy. Methods: Patients with clinically active pSS [EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) ≥6] were randomised to receive either 600 mg SC iscalimab weekly on 4 occasions, followed by 300 mg SC weekly until week 12, or a single IV dose of 10 mg/kg iscalimab on study Day 1, followed by 300 mg SC weekly until week 12. Subjects and investigator staff remained blinded to study treatment allocation until first dosing. Results: Twenty-five patients were randomised; 13 in the SC loading and 12 in the IV loading arms. Baseline characteristics were similar to the previous phase IIa cohorts with mean ESSDAI scores of 12.7 (SD 6.1) and 10.4 (5.9) in the SC and IV loading arms respectively. In Arm 1 (SC) and Arm 2 (IV), the mean trough plasma concentrations were 169 μg/mL (SD 64.1, CV 38%) and 135 μg/mL (SD 70.9, CV 53%) on Day 85, respectively. Both values were well above levels previously reported to be sufficient for suppression of germinal centre development and T dependent antigen responses in cynomolgus monkeys. Consistent with this finding, clinically important improvements were seen in both arms with a mean decrease in ESSDAI scores of -5.5 (+/- SD: 5.5) and -7.6 (+/- 7.1) points from baseline to Day 85 in the SC and IV dosing arms. Improvements were also seen in EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI) scores: -1.67 (+/- 1.8) and -1.17 (+/- 2.3), respectively. Other secondary efficacy outcomes showed similar patterns of improvement. Treatment with iscalimab was associated with a reduction in the germinal centre-related serum biomarker CXCL13 in both groups. Overall, iscalimab was safe and well-tolerated with no new safety signal emerging. One subject experienced three SAEs (hemarthrosis, worsening of right knee pain and swelling requiring arthroscopy) in the safety follow-up period, all unrelated to study drug. Conclusion: These results further support the safety and efficacy of iscalimab in pSS and the suitability of SC dosing for future development. Disclosure of Interests: Benjamin Fisher Consultant for: Novartis, Roche, MedImmune, Bristol-Myers Squibb, Antónia Szántó: None declared, Wan Fai Ng: None declared, Michele Bombardieri Grant/research support from: Celgene, Consultant for: Medimmune, Maximilian Posch: None declared, Athena Papas Grant/research support from: Novartis, Consultant for: Novartis, Arwa Farag: None declared, Thomas Daikeler: None declared, Bettina Bannert: None declared, Alan Kivitz Shareholder of: Novartis, Consultant for: Abbvie, Janssen, Pfizer, UCB, Genzyme, Sanofi, Regeneron, Boehringer Ingelheim, Sun Pharma Advanced Research, Flexion., Paid instructor for: Celgene, Horizon, Merck, Novartis, Pfizer, Genzyme, Sanofi, Regeneron, Speakers bureau: Celgene, Horizon, Merck and Genetech, Flexion, Steven Carsons Grant/research support from: Novartis, David Isenberg: None declared, Francesca Barone Grant/research support from: GlaxoSmithKline, Roche, UCB Pharma, Actelion, ONO Pharmaceutical, Consultant for: GlaxoSmithKline, Roche, Actelion, ONO Pharmaceutical, Simon J. Bowman Grant/research support from: Previously UCB Pharma (to University of Birmingham) and Roche, Consultant for: 2016-7: Novartis, Mitsubishi Tanabe Pharma 2017-8: AstraZeneca, MedImmune, GFK, Xtlbio, ONO Pharmaceutical 2018-9: Novartis, AstraZeneca, UCB Pharma, Pascal Espie Employee of: Novartis, Grazyna Wieczorek Employee of: Novartis, Pierre Moulin Employee of: Novartis, David Floch Employee of: Novartis, Cyrielle Dupuy Employee of: Novartis, Amanda Nguyen Employee of: Novartis, Andrew Wright Shareholder of: Novartis, Employee of: Novartis, Michael Rotte Employee of: Novartis, James Rush Employee of: Novartis, Peter Gergely Employee of: Novartis